2017
DOI: 10.3141/2639-01
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effects of Rising Groundwater from Sea Level Rise on the Service Life of Pavements in Coastal Road Infrastructure

Abstract: Coastal communities with road infrastructure close to the shoreline are vulnerable to the effects of sea level rise caused by climate change. The sea level in coastal New Hampshire is projected to rise by 3.9 to 6.6 ft (1.2 to 2.0 m) by 2100. Climate change vulnerability and adaptation studies have focused on surface water flooding caused by sea level rise; however, little attention has been given to the effects of climate change on groundwater. Groundwater is expected to rise with sea level rise and will inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 15 publications
3
46
0
Order By: Relevance
“…Notable SLR induced impacts are already occurring in coastal areas nationwide in the form of road closures and roadway degradation 36 . Here we focus on roadway failure owing to water depth and inability of cars to traverse, although it is understood that damages such as rutting and potholing will likely result from the presence of shallow water tables 37 . Assessment of such damages is outside the scope of this study and is recommended for future work.…”
Section: Study Objectivesmentioning
confidence: 99%
“…Notable SLR induced impacts are already occurring in coastal areas nationwide in the form of road closures and roadway degradation 36 . Here we focus on roadway failure owing to water depth and inability of cars to traverse, although it is understood that damages such as rutting and potholing will likely result from the presence of shallow water tables 37 . Assessment of such damages is outside the scope of this study and is recommended for future work.…”
Section: Study Objectivesmentioning
confidence: 99%
“…These facilities not only require huge economic investment in the manufacturing process but also are closely related to personal safety. The facilities' service life is usually decades or even hundreds of years [1,2]. In the course of using, they could inevitably be coupled with various disasters (such as environmental loads, fatigue effects, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…Their analysis showed that climate change has a significant impact on the service life of concrete. Knott et al (2017) presented the effects of rising groundwater, caused by sea level rise, on the service life of pavements in the coastal road infrastructure. The results indicated that service life reduction depended on the current depth to groundwater, the pavement structure, and the subgrade.…”
Section: Introductionmentioning
confidence: 99%